TAKING CHARGE OF COPD: EVALUATING SELF-MANAGEMENT PROGRAMS’ EFFECTIVENESS IN ELDERLY PATIENTS - Abdel-Aziz, Amina Mahmoud; Abdullah , Ahmed Al-Mansour (Research Journal of Health, Medicine and Nursing, 2024)
Chronic obstructive pulmonary disease (COPD) is a progressive, inflammatory lung condition characterized by chronic airflow limitation, primarily caused by obstructive bronchitis and emphysema. This debilitating disease predominantly affects the elderly population, becoming more prevalent in individuals aged over 60. It is a leading chronic disease in this demographic, impacting around 16% of those over 65 years globally. COPD poses a significant threat to elderly individuals' health and quality of life, ranking as the fourth leading cause of death and the twelfth leading cause of disability in this age group. The World Health Organization predicts that by 2020, COPD will become the third leading cause of death and the fifth leading cause of disability worldwide. Elderly COPD patients face various physical and psychosocial challenges that substantially affect their quality of life. Physically, symptoms like dyspnea, cough, fatigue, and sleep disturbances are common and contribute to disability, limiting their motivation, concentration, and daily activities. These limitations extend to activities of daily living, household chores, and social and leisure activities. Psychosocially, feelings of depression and anxiety are prevalent in these patients, often accompanied by social issues like a loss of social role and a tendency to avoid interactions and recreational activities. These problems have a profound impact on their physical functioning, independence, overall well-being, and health outcomes